Dinâmica fluvial e qualidade da água da bacia de drenagem do ribeirão Maringá : contribuição para o planejamento e gestão ambiental - Coelho, Adilson Rodrigues (2007)
Maringá City is located in the water divisor within the basins of the rivers Pirapó and Ivaí. The existing hydrographic basins in the municipality are constituted by small order sub-basins of the river Pirapó basin (Maringá riverside and Morangueira riverside, North quadrant of the city) and of the river Ivaí basin (Pingüim riverside, South quadrant). The heads of this drainage are inside the urban site, being their development towards the rural areas. A consequence of this peculiar situation is the strong vulnerability of the city's water resources facing the polluting agents produced by anthropic activity, receiving effluents produced both in the city as well as in the rural area. The environmental degradation, resulting from this, is easily recognized even after a brief observation. In the drainage there is the occurrence of garbage together with organic and inorganic chemical compounds which induce, in certain times of the year, visible alterations in water quality. This study analyses the geoenvironmental characteristics of the hydrographic basin of Maringá riverside through the integration of water physicochemical data, base geomorphology, and characteristics of anthropic action. The production of sediments in the basin was monitored through the concentration of sedimentary load hydrotransported in the fixed points of the sampling collection. It presents the characteristics of the hydrographic basin of Maringá riverside, contemplating biotic, abiotic and anthropic aspects which inter-relate in the basin, in order to understand the dynamics that rule these physicochemical processes and their implications in the basin urbanization. Hence, during six years, water samples were collected in five monitoring points of the basin. The variation in water physicochemical characteristics was evaluated monthly as well as the concentration of the heavy metals Cd, Pb, Cr, Fe, Cu, Mn, Zn, Ni, and Co. The different metal percentages were related to the different rates of precipitation and flow in the five monitored points, concerning the use and soil occupation. In the sample collections the following were measured: pH, temperature, transparence, dissolved oxygen. The sediment load in the sample points underwent granulometrical analysis and compared to the flows that carried it, rating curve flow was used, sediments with different granulometries were distributed heterogeneously along the water column. Through the results, it may be concluded that the heavy metals cause an impact to the basin breaking the limits of CONAMA 357/ 2005 resolution, due to anthropic activity performed in it.